2009
DOI: 10.1111/j.1365-2648.2008.04914.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nursing documentation – research designs and methods: systematic review

Abstract: The use of structured nursing terminology in electronic patient record systems will extend the scope of documentation research from assessing the quality of documentation to measuring patient outcomes. More data should also be collected from patients and family members when evaluating nursing documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
0
30

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 50 publications
2
122
0
30
Order By: Relevance
“…A structured format for recording has been effective at increasing the quality of nursing documentation [39,49]. A study conducted in a Swedish hospital showed that both the quality and comprehensiveness of PU documentation significantly improved after implementing an EHR system with pre-formulated templates [39]; however, the study had a before-after design with no control group.…”
Section: Discussionmentioning
confidence: 99%
“…A structured format for recording has been effective at increasing the quality of nursing documentation [39,49]. A study conducted in a Swedish hospital showed that both the quality and comprehensiveness of PU documentation significantly improved after implementing an EHR system with pre-formulated templates [39]; however, the study had a before-after design with no control group.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of information about clients and care in the operation of modern health care organisations has been well recognized [1,2,3]. Information systems that facilitate data collection and tracking for patient care can also sustain care quality improvement [4].…”
Section: Introductionmentioning
confidence: 99%
“…A review suggests that standardized documentation is associated with more positive than negative effects, for example regarding main outcomes as quality and content. [4] Also, documentation has been shown to be important in relation to mortality, as it was found that certain patterns of nursing documentation within electronic health records could be used to predict patient mortality. [43] An ethnographic study carried out in a medical ED found that nurses tended to document screenings supporting a flow culture, where the primary objective for ED nurses were to secure free beds for the next patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Furthermore, documentation is necessary for patient safety and continuity. [3][4][5] Even though documenting patient data has been a nursing task for more than 150 years, [6] and the exchange of information is a significant nursing activity, [3] documentation practices is still today an area of extensive challenges. [7][8][9][10][11] Increased requirements for documentation and demands to fulfill quality standards are a part of everyday practice in Danish hospitals, as patient treatment and trajectories are getting more complex.…”
Section: Introductionmentioning
confidence: 99%